2002
DOI: 10.1203/00006450-200211000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Thyroid Carcinoma That Express Sodium-Iodide Symporter Have a Lower Risk of Recurrence for Children and Adolescents

Abstract: The sodium-iodide symporter (NIS) is expressed by papillary (PTC) and follicular (FTC) thyroid carcinoma, and is essential for iodine uptake. We hypothesized that PTC and FTC with detectable NIS immunostaining would be more amenable to radioactive iodine ( 131 I) treatment and follow a more benevolent course. To test this, we determined NIS expression by immunohistochemistry in 23 PTC, 9 FTC, and 12 benign thyroid lesions from children and adolescents. NIS expression was determined by two blinded examiners and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 38 publications
0
32
0
2
Order By: Relevance
“…The former study assessed the expression of NIS in the malignant tumor and compared to benign lesions as a substitute of normal thyroid. The authors did not find a significant difference between benign and malignant thyroid lesions (Patel et al 2002). Because the overall recurrence risk was increased for those tumors that had undetectable NIS expression, the authors suggested that NIS expression is a favorable prognostic indicator for DTC in children and adolescents (Patel et al 2002).…”
Section: Other Fusions Transcriptsmentioning
confidence: 94%
See 3 more Smart Citations
“…The former study assessed the expression of NIS in the malignant tumor and compared to benign lesions as a substitute of normal thyroid. The authors did not find a significant difference between benign and malignant thyroid lesions (Patel et al 2002). Because the overall recurrence risk was increased for those tumors that had undetectable NIS expression, the authors suggested that NIS expression is a favorable prognostic indicator for DTC in children and adolescents (Patel et al 2002).…”
Section: Other Fusions Transcriptsmentioning
confidence: 94%
“…The authors did not find a significant difference between benign and malignant thyroid lesions (Patel et al 2002). Because the overall recurrence risk was increased for those tumors that had undetectable NIS expression, the authors suggested that NIS expression is a favorable prognostic indicator for DTC in children and adolescents (Patel et al 2002). Additionally, the authors studied patients up to 21 years of age and only two cases under the age of 10.…”
Section: Other Fusions Transcriptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Указанные молекулярные различия могут являться одним из благоприятных условий лучшего ответа на РЙТ у детей, чем у взрослых с ПРЩЖ, что, вероятно, объ-ясняет более низкую смертность и более редкое про-грессирование до низкодифференцированных типов опухолей у детей. В подтверждение этой гипотезы приводится небольшое исследование у детей (n = 23), в котором было выявлено, что наличие отдаленных метастазов и рецидивов рака было ассоциировано только с опухолями с неопределяемым при иммуно-гистохимическом анализе НЙС, а для достижения ремиссии в этих случаях потребовались значительно большие дозы радиоактивного йода [12].…”
Section: из раздела "актуальность"unclassified